PONDOK DAMAI: A STUDY OF PELITA INTERFAITH ASSOCIATION MOVEMENT FOR INTERRELIGIOUS ENGAGEMENT IN INDONESIA - Syafira Anisa (UIN Raden Mas Said Surakarta, 2022)
Indonesia possesses various religions and faith affiliations, so there is no doubt that there are multiple causes that have conflict due to several factors such as economic, social, and political. To minimize the possibility of the emergence of intolerance and discrimination, 'Pelita,' an interfaith association, seeks to realize the values of interreligious harmony among religious people, one of which is located in Semarang. Pelita aimed for the nation's adolescents to return to knitting peace in its annual plan, 'Pondok Damai’. This paper analyzed how the adolescents' activities in Pondok Damai are strongly oriented toward maintaining interreligious engagement. Using qualitative methods through a sociological approach, this paper interviewed participants involved in Pondok Damai and relevant literature research. Moreover, this paper used an analysis belonging to J.B Banawiratma, ‘Seven Moments of Dialogue’. Using the theory of Seven Moments of Dialogue, the author will interpret several Pondok Damai activities and how it contributes to interreligious dialogue in Indonesia. These moments contain dialogue of life, social analysis and contextual ethical reflection, study of religious traditions, interfaith dialogue in sharing faith and interfaith theology, dialogue of action and intra-religious dialogue. This research concluded that Pondok Damai became a forum for interfaith encounters with youngsters from different affiliations. Through their participation in a series of Pondok Damai activities, youngsters have established a true peace by interreligious engagement among them.